Metode Al-Jam’u dalam Penyelesaian Hadis Mukhtalif tentang Persaksian : Riwayat Muslim no. indeks 1719 dengan Bukhari no. indeks 2457 - Alfani, Mukhammad; Athoillah Umar (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2023)
The Prophetic Hadith is the second source of Islamic law after the Quran. The Quran mentions many legal issues on a global scale, while the Prophet's hadith details these issues so that they can be understood by Muslims. In addition to serving as an explanation for the Quran, the Prophet's hadith is also a source of Islamic law to complement the Quran. Therefore, the accuracy of the Prophetic traditions is of great concern to Muslims. One of the roles of scholars is to solve the problem of conflicting traditions (mukhtalif traditions). There are contradictions in the prophetic traditions, there are mukhtalif traditions and mushkil traditions are terms used to describe conflicting traditions. The factors that lead to contradictions in traditions include differences in the time, place and situation when the traditions were spoken. Scholars have endeavored to clarify the Prophet's traditions and explain any contradictions so that the authenticity of the traditions is preserved and not exploited by irresponsible parties to the detriment of Islam. This study uses the descriptive-analytical method to analyze the significance of the issue of hadith contradictions. Therefore, this study provides a critical perspective on the understanding of hadith related to ikhtilaf al-hadis especially on the hadith about testimony with the al-jam'u method.